Assessment of Genetic Diversity among Musa Cultivars based on Sequence-Related Amplified Polymorphism Technique - Boonsrangsom, Thanita; Phetnin, Busaraporn; Ratanasut, Kumrop; Sujipuli, Kawee (Naresuan University Journal: Science and Technology (NUJST); Vol 28 No 2 (2020): April-June 2020DO - 10.14456/nujst.2020.15, 2020)
Bananas are one of the world’s most eatable fruits. Edible bananas belonging to the Eumusa section are believed to contain genomes from two wild diploid species, Musa acuminata Colla (A genome) and M. balbisiana Colla (B genome). Almost cultivated bananas are diploid, triploid or tetraploid and classified into different genome groups according to several morphological characteristics. ‘Kluai Namwa Mali-Ong’ is the most suitable use as a raw material for the sun-dried banana production in Bangkratum District, Phitsanulok Province, Thailand. The varietal identification among hybrid bananas is difficult due to there is a small difference in morphological characters and local names of bananas based on fruit traits results in abundant synonyms of banana cultivars. Therefore, it is essential for choosing the correct banana cultivars for marketing and gaining understanding of banana breeding using biotechnology approaches. The study aimed to assess the genetic diversity among Musa (ABB group) ‘Kluai Namwa’ cultivars and two outgroup taxa (AA/AAA and BB groups) with DNA markers. Based on ten sequence-related amplified polymorphism (SRAP) markers, a total of 80 DNA bandings were scored, of which 74 were polymorphic (92.50%). Polymorphic information content (PIC) values ranged from 0.16 to 0.30 with an average 0.25. The bands size ranged from 100 to 1200 base pairs. An unweighted pair group method arithmetic average (UPGMA) analysis based on Dice coefficients demonstrated that the accessions had a similarity range from 0.42 to 1.00 with a mean of 0.86 which suggested extreme genetic diversity among Musa samples. However, the low genetic diversity was found among 12 Musa (ABB group) ‘Kluai Namwa’ samples. In the present study, dendrogram derived from ten SRAP markers showed that all samples could be categorized into two major groups (ABB-BB and AA/AAA genome groups). The results based on SRAP markers in this study could be useful for germplasm collection and banana breeding in the future. Keywords: genetic diversity, banana, Musa , DNA marker, SRAP